Prospects for hydrogen production by the method of gasification of MSW at operating TPPs - Kolbantseva, D.L.; Treshchev, D.A.; Kalmykov, K.S.; Anikina, I.D.; Treshcheva, M.A.; Kalyutik, A.A.; Vladimirov, Ya.A.; Naypak, K.A. (International journal of hydrogen energy, 2024)
The work is devoted to the development of a thermal scheme for the conversion of a cogeneration power plant to threegeneration with the production of hydrogen as a new product. The purpose of the work is to assess the possibility and potential of hydrogen production from MSW at the existing thermal power plants of St. Petersburg. To achieve this goal, it is necessary to develop a methodology for selecting the site of an existing thermal power plant in order to integrate a hydrogen production complex by the MSW gasification method, as well as a methodology for estimating the amount of hydrogen that can potentially be obtained from a given amount of MSW. The research methods include simulation of the thermal circuit of a steam power plant in the United Cycle program. The paper proposes an algorithm for selecting the site of an operating thermal power plant for the integration of a complex for the production of hydrogen by the method of MSW gasification. The algorithm can be applied to any subjects of the Russian Federation, and its relevance is confirmed by strategic documents. Potential locations for the new TPP are being considered in the territories of TPP-21 and TPP-22, which have the necessary resources and good infrastructure. As a result of the study, the site of TPP-22 was selected as the most suitable for the placement of new facilities. A new thermal scheme of a threegeneration power plant has been developed, including a hydrogen generation unit by the MSW gasification method. This allows the production of hydrogen in parallel with the production of electricity and heat. The efficiency evaluation criterion is the fuel heat utilization factor (FHUF). Regardless of the hydrogen content in the generated synthesis gas, the integration of the synthesis gas cooler into the thermal circuit of the TPP leads to an increase in the FHUF and an additional energy effect. This scheme increases the efficiency of existing TPP plants, regardless of the morphological composition of municipal solid waste.